Engineering the Protein Corona Structure on Gold Nanoclusters Enables Red‐Shifted Emissions in the Second Near‐infrared Window for Gastrointestinal Imaging. Issue 50 (4th October 2020) - Wang, Weili; Kong, Yifei; Jiang, Jun; Xie, Qianqian; Huang, Yang; Li, Guanna; Wu, Di; Zheng, Huizhen; Gao, Meng; Xu, Shujuan; Pan, Yanxia; Li, Wei; et al.
Abstract: The application of NIR‐II emitters for gastrointestinal (GI) tract imaging remains challenging due to fluorescence quenching in the digestive microenvironment. Herein, we report that red‐shifting of the fluorescence emission of Au nanoclusters (AuNCs) into NIR‐II region with improved quantum yields (QY) could be achieved by engineering a protein corona structure consisting of a ribonuclease‐A (RNase‐A) on the particle surfaces. RNase‐A‐encapsulated AuNCs (RNase‐A@AuNCs) displayed emissions at 1050 nm with a 1.9 % QY. Compared to rare earth and silver‐based NIR‐II emitters, RNase‐A@AuNCs had excellent biocompatibility, showing >50‐fold higher sensitivity in GI tract, and migrated homogenously during gastrointestinal peristalsis to allow visualization of the detailed structures of the GI tract. RNase‐A@AuNCs could successfully examine intestinal tumor mice from healthy mice, indicating a potential utility for early diagnosis of intestinal tumors. Abstract : The precise control of the surface protein corona enabled the red‐shifting of the emission of gold nanoclusters (AuNCs) into the NIR‐II region. RNAse‐A‐encapsulated AuNCs allowed the visualization of the detailed structures of the GI tract during gastrointestinal peristalsis, providing a non‐invasive and X‐ray‐free technique to differentiate intestinal tumours.